2019
DOI: 10.3390/genes10100751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fat and Fatty Acids on the Formation of Autolysosomes in the Livers from Yellow Catfish Pelteobagrus Fulvidraco

Abstract: The autophagy-lysosome pathway, which involves many crucial genes and proteins, plays crucial roles in the maintenance of intracellular homeostasis by the degradation of damaged components. At present, some of these genes and proteins have been identified but their specific functions are largely unknown. This study was performed to clone and characterize the full-length cDNA sequences of nine key autolysosome-related genes (vps11, vps16, vps18, vps33b, vps41, lamp1, mcoln1, ctsd1 and tfeb) from yellow catfish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…Fatty acid is the directly factor that regulated intracellular lipid level. In the present study, we found that FA incubation markedly increased lipid and NEFA level in hepatocytes from yellow cat sh, in agreement with other studies (Wu et al 2019;Wu et al 2020;Song et al 2020). In addition, FA incubation signi cantly reduced the mRNA and the protein level of PI3KC3, but increased the mRNA and the protein level of PPARα and PPARγ.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Fatty acid is the directly factor that regulated intracellular lipid level. In the present study, we found that FA incubation markedly increased lipid and NEFA level in hepatocytes from yellow cat sh, in agreement with other studies (Wu et al 2019;Wu et al 2020;Song et al 2020). In addition, FA incubation signi cantly reduced the mRNA and the protein level of PI3KC3, but increased the mRNA and the protein level of PPARα and PPARγ.…”
Section: Discussionsupporting
confidence: 94%
“…FA was added as a mixture of palmitic acid and oleic acid at a ratio of 1:1. The form and the concentration of FA were selected according to our pilot trial and the publications of the in vitro studies (Wu et al 2019;Wu et al 2020; Chen et al 2020a; Song et al 2020). Then, after 24 h incubation, cells were collected to determine the promoter activity, based on the manufacturer's instruction of the Dual-luciferase Reporter Assay System (Promega).…”
Section: Sequence Analysismentioning
confidence: 99%
“…When lower than the optimal lipid level, feed nutrients were insufficient or unbalanced to meet the lipid and energy requirements of fish body growth (Rahimnejad et al., 2015). When higher than the optimal lipid level, the higher lipid could result in excessive deposition of fish body fat, stressing response, damaging liver function and reducing growth (Tian et al., 2015; Wu et al., 2019). High dietary lipid levels could lead to a decline in growth and feed utilization for tilapia and cause a substantial increase in intraperitoneal fat deposition (Chang et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, PA increased TG content, but reduced ME and FAS activities, and mRNA concentrations of 6pgd , fas , acca and cd36 . Studies in our laboratory pointed out that PA elevated NEFA content and regulated gene expression of lipid absorption in hepatocytes of yellow catfish [ 33 ]. The decreased gene expression and enzymatic activities related to lipid absorption as well as lipogenesis contributed to suppress lipid accumulation [ 3 ].…”
Section: Discussionmentioning
confidence: 99%